2019
DOI: 10.1590/0001-3765201920180694
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the biodegradation of chlorpyrifos-methyl by Bacillus megaterium CM-Z19 and Pseudomonas syringae CM-Z6

Abstract: The strains CM-Z19 and CM-Z6, which are capable of highly degrading chlorpyrifos-methyl, were isolated from soil. They were identified as Bacillus megaterium CM-Z19 and Pseudomonas syringae CM-Z6, respectively, based on the 16S rRNA and an analysis of their morphological, physiological and biochemical characteristics. The strain CM-Z19 showed 92.6% degradation of chlorpyrifos-methyl (100 mg/l) within 5 days of incubation, and the strain CM-Z6 was 99.1% under the same conditions. In addition, the degradation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 28 publications
(13 reference statements)
3
11
0
1
Order By: Relevance
“…Physiological characteristics of Gram-negative bacteria, such as Enterobacter, allow the bacteria to be more effective in degrading pesticides compared to Gram-positive bacteria, especially the chlorpyrifos insecticide (Singh et al 2004). Zhu et al (2019) comparing the ability of Bacillus megaterium and Pseudomonas syringae to degrade the chlorpyrifos insecticide, and the results showed that P. syringae had a better ability to degrade chlorpyrifos insecticide up to 99%, while B. megaterium was able to degrade chlorpyrifos insecticide up to 92%.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological characteristics of Gram-negative bacteria, such as Enterobacter, allow the bacteria to be more effective in degrading pesticides compared to Gram-positive bacteria, especially the chlorpyrifos insecticide (Singh et al 2004). Zhu et al (2019) comparing the ability of Bacillus megaterium and Pseudomonas syringae to degrade the chlorpyrifos insecticide, and the results showed that P. syringae had a better ability to degrade chlorpyrifos insecticide up to 99%, while B. megaterium was able to degrade chlorpyrifos insecticide up to 92%.…”
Section: Discussionmentioning
confidence: 99%
“…Some strains, such as Pseudomonas sp. and Bacillus megaterium, have been able to degrade CP (100 mgL −1 ) but not completely TCP (Barman et al 2014: Zhu et al 2019. This situation may be re ected with the accumulation of TCP and other intermediates, which prevents the complete elimination of the parent compound (Barman et al 2014) and may allow further dissipation of contaminants, as e.g.…”
Section: Tolerance and Biodegradation Of Chlorpyrifosmentioning
confidence: 99%
“…One of the closest genera to Azotobacter that has shown e ciency in CP degradation is Pseudomonas, as it can use it as a carbon source and energy (Gilani et al 2016); and it has been particularly documented in strains such as ATCC 700113 (Feng et al 1988). Pseudomonas syringae was able to degrade 99.1% of 100 mg L −1 of CP in 5 d also presenting degradation-associated phosphoesterase enzymatic activity (Zhu et al 2019). However, the initial concentration is important and another limiting factor in CP degradation.…”
Section: Tolerance and Biodegradation Of Chlorpyrifosmentioning
confidence: 99%
“…R ecently, a b ioremediation tool consisting of live cells of A. aurescens TC1 has been successfully used to repair the terbuthylazine-contaminated soil (Viegas et al 2019, Silva et al 2015. This method required prior acquisition of pure strains or microbial consortium with high degradation performance ( Zhu et al 2019c, Sagarkar et al 2014, Lu et al 2020, Kou et al 2020). In addition, many factors such as temperature, pH and oxygen content usually affect the biodegradation of terbuthylazine (Mueller et al 2010, Getenga et al 2009, Zhao et al 2019, Hou et al 2019.…”
Section: Introductionmentioning
confidence: 99%